2011
DOI: 10.3109/09637486.2011.607801
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Hepatoprotective effects on alcoholic liver disease of fermented silkworms withBacillussubtilisandAspergillus kawachii

Abstract: The purpose of this study was to investigate the protective effect of Bacillus subtilis fermented silkworm powder (BFSP) and Aspergillus kawachii fermented silkworms powder (AFSP) on alcohol-induced hepatotoxicity in Sprague-Dawley rats. Alcohol-feeding rats were fed with diets containing silkworm powder (SP) or both BFSP and AFSP at the 5% (w/w) levels for 4 weeks. Alcohol administration resulted in a significant increase in the activities of liver marker enzymes, aspartate aminotransferase (AST), γ-glutamyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Such a reduction in the fat pads was believed to contribute to suppressing an increase in body weight. Also, the study which caused the formation of alcohol-induced fatty livers in rats and then treated them with a fermented silkworm pupae powder for 4 weeks reported that the fatty droplets in the fatty livers were diluted [21]. Given this, it was expected that similar reductions in fat pads could occur in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Such a reduction in the fat pads was believed to contribute to suppressing an increase in body weight. Also, the study which caused the formation of alcohol-induced fatty livers in rats and then treated them with a fermented silkworm pupae powder for 4 weeks reported that the fatty droplets in the fatty livers were diluted [21]. Given this, it was expected that similar reductions in fat pads could occur in various tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a growing interest in insect-based bioactive products has been accompanied by an increasing demand for alternative protein sources. Some insect-derived natural products and their components have been found to have bioactivity, exerting antioxidant, anti-inflammatory, hepatoprotective, and anti-obesity effects [9,10,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the utilization of pupal extract can lead to the development of new products, such as antioxidants, cosmetics and anti-aging therapies15. It was reported recently that fermented pupa powder has a protective effect in alcohol-induced hepatotoxicity in a rat model16. There are few studies in the literature, however, of silkworm pupae as raw materials for chemical industries.…”
mentioning
confidence: 99%